Spatial Interactions and Price Transmission in Yam Markets in Côte d’Ivoire - Koffi Celestin, N’goran; Sylvie, Eza (European Scientific Journal, ESJ, 2023)
Spatial interactions are essential factors in the process of price transmission. However, very few studies have taken these factors into account in the analysis of price transmission. This study attempts to analyze the price transmission in the yam markets in Côte d’Ivoire by emphasizing on spatial interactions. To do this, based on the two types of data, rainfall and the price series of four varieties of yams (kponan, krenglè, assawa and bêtè-bètè) and cassava, the dynamic Durbin spatial model has been used. The results show that prices are transmitted both between markets and yam varieties. Indeed, the prices of krenglè and assawa varieties influence the price of the kponan variety. The rainfall also increases the price of the kponan variety. Therefore, it would be important to take into account the different varieties of yam in price stability reforms and encourage producers to produce more of these varieties. Out-of-season production will prevent risks from climatic hazards.